Contribution to the taxonomy of Lobellini (Collembola: Neanurinae) and investigations on luminous Collembola from Japan - Ohira, Atsuko; Nakamori, Taizo; Matsumoto, Sachi; Bessho-Uehara, Manabu; Kato, Takumi; Oba, Yuichi (Zootaxa, 2023)
Lobella sauteri was redescribed based on the lectotype and specimens obtained from the type locality Bugenji, Yokohama, Kanagawa, as the true identity of the luminous Collembola, Lobella sp. Lobella sauteri has morphological traits characteristic of the genus currently called Telobella. As L. sauteri is the type species of Lobella, the genus Telobella was synonymised with Lobella according to the principle of priority, and the genus Lobella was redefined to include both the species previously assigned to Telobella and those previously assigned to Lobella. A new species Lobella monstrum sp. nov. was described and new combinations were proposed for certain species in Lobellini. Light-emitting capacity was confirmed in L. sauteri and newly reported in Lobella yambaru comb. nov. Vitronura giselae and Vitronura kunigamiensis.